Effect of Grassland Vegetation Units on Soil Biochemical Properties and the Abundance of Selected Microorganisms in the Obra River Valley - Justyna Mencel; Anna Wojciechowska; Agnieszka Mocek-Płóciniak (Agronomy)
The study examined seasonal variability in soil enzymatic activity and microbial abundance across five grassland vegetation units: Molinietum caeruleae, Alopecuretum pratensis, Arrhenatheretum elatioris, Lolio–Cynosuretum, and com. Poa pratensis–Festuca rubra. Soils under Molinietum caeruleae showed higher fungal abundance and greater plant diversity, while Lolio–Cynosuretum was notable for elevated Azotobacter spp. populations. Actinobacteria preferred soils with more organic matter, whereas Azotobacter spp. favored higher pH. A negative correlation was observed between the Shannon diversity index (H′) and heterotrophic bacterial abundance in Arrhenatheretum elatioris and with fungal abundance in com. Poa pratensis–Festuca rubra. Acid and alkaline phosphatase and catalase activities were also negatively correlated with H′. Redundancy analysis showed these enzymes were related to total nitrogen content, and enzyme activity decreased with rising soil pH. In autumn 2022, high fungal abundance coincided with a reduction in other microorganisms. Seasonal trends were evident: catalase and urease activities peaked in autumn 2023, while other enzymes were more active in spring 2022. The results emphasize the significance of seasonal shifts in shaping microbial and enzymatic soil processes, which are vital for nutrient cycling, carbon sequestration, and climate regulation. Further research is essential to guide sustainable grassland soil management.